Consumer culture theory in Asia : history and contemporary issues - Minowa, Yuko; Belk, Russell W. (New York, NY : Routledge, 2022)
"We live in times of increasing world uncertainty. Consumer culture in Asia has embodied such precariousness, with their unprecedented states of both prosperity and vulnerability. Works in this volume examine the consumer cultures that exist in today's precarious Asia. They do this through culturally oriented, critical consumer research. How deeply has the consumer precariousness in Asia been intertwined with the sociohistoric patterning of consumption including class, gender, and other social categories? How do these problematics affect consumers' identity projects, consumer rituals, and marketplace cultures? How is consumer precariousness aggravated by the governmentality of the superpower? How does the changing landscape of inter-Asian and global popular culture impact consumer culture in these nations? Together, the authors in this volume attempt to answer these questions through consumer research within the paradigm known as consumer culture theory (CCT). Since most CCT inquiry has been in Western contexts, this volume augments the existing knowledge. It presents the most current, critical, historical, and material consumer studies focused on Asia. This volume will be of interest to seasoned CCT researchers and academics, for anyone new to consumer culture theory, and for postgraduate students interested in CCT or writing a consumer culture related thesis"--
1 Introduction Yuko Minowa and Russell W. Belk SECTION I History of Consumerism in Asia 2 The Long March of the Commodity in China Alison Hulme 3 Consumerism in Early Modern Japan: Food, Fashion, and Publishing Kazuo Usui SECTION II Consumer Identity Projects 4 Century of Humiliation and Consumer Culture: The Making of National Identity I-Chieh Michelle Yang, Juliana French, and Christina Lee 5 Predicting a Mother's Role in Investing in Children's Education: A Study on Autonomy and Empowerment from India Akshaya Viayalakshmi, Meng-Hsien (Jenny) Lin, and Sarah Ricks SECTION III Consumer Rituals 6 Gift-giving and Kinship-making: Male Phoenix in China Jia Cong and Xin Zhao 7 Solitary Death is Elsewhere: The Making of Memorial Community in Japan Yuko Minowa 8 The Work of Culture in Thai Theravāda Buddhist Death Rituals Rungpaka Amy Hackley SECTION IV Governance and Sustainability in Consumption Practices 9 Utopia and Dystopia: Consumer Privacy and China's Social Credit System Eric Ping Hung Li, Guojun (Sawyer) He, Magnum Man Lok Lam, and Wing-sun Liu 10 The Thanatopolitics of Neoliberalism and Consumer Precarity Rohit Varman and Devi Vijay 11 Cold Chains in Hanoi and Bangkok: Changing Systems of Provision and Practice Jenny Rinkinen, Elizabeth Shove, and Mattijs Smits SECTION V Body, Technology, and Mass-Mediated Marketplace Ideologies 12 Market Versus Cultural Myth: A Skin-deep Analysis of the Fairness Phenomena in India Anoop Bhogal-Nair and Andrew Lindridge 13 Haptic Creatures: Tactile Affect and Human-Robot Intimacy in Japan Hirofumi Katsuno and Daniel White
Keywords: Consumer behavior -- Asia; Consumption (Economics) -- Asia; BUSINESS & ECONOMICS / Marketing / General; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Corporate & Business History